Physiological and stroke parameters to assess aerobic capacity in swimming - Oliveira, M. F. M.; Caputo, F.; Lucas, R. D.; Denadai, B. S.; Greco, C. C. (International Journal of Sports Physiology and Performance, 2012)
Purpose: To identify the speed corresponding to anaerobic threshold using the D-max method for both blood lactate and biomechanical stroke parameters determined in an incremental swimming test and to compare this information with the speed corresponding to the maximal lactate steady state (SMLSS). Methods: Five male long-distance swimmers and 8 triathletes (N = 13; age 23.8 ± 9.5 y, height 1.76 ± 0.1 m, weight 71.3 ± 9.8 kg) performed the following protocols: maximal 400-m test to determine maximal aerobic speed (S400); 7 × 200-m incremental test to determine the speed corresponding to the D-max point on the blood lactate (SLa), stroke-rate (SSR), stroke-length (SSL), and stroke-index (SSI) responses; and two to four 30-min submaximal tests to determine the SMLSS. Results: SLA (1.18 ± 0.08 m/s), SSI (1.18 ± 0.08 m/s), SSR (1.17 ± 0.1 m/s), and SSL (1.16 ± 0.09 m/s) were not significantly different from each other or from SMLSS (1.13 ± 0.08 m/s). There were high correlations between SLA, SSI, SSR, SSL, and SMLSS (r = .91, .89, .85, and .80, respectively). The typical errors of estimate for SLA (3.2%), SSI (3.7%), SSR (4.1%), and SSL (4.7%) suggest good validity of these variables to predict SMLSS. Furthermore, all physiological and biomechanical variables were moderately to highly correlated with S400 (r = .73-.95). Conclusions: It is possible to obtain a physiological index of aerobic capacity and performance using simple biomechanical measurements during an incremental test without performing blood lactate analyses.